2014
DOI: 10.1634/theoncologist.2014-0058
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in the Trastuzumab for Gastric Cancer Trial

Abstract: Background. The Trastuzumab for Gastric Cancer phase III trial demonstrated that combining trastuzumab with chemotherapy significantly improved overall survival compared with chemotherapy alone in HER2‐positive advanced gastric or gastroesophageal junction cancer. We report health‐related quality of life (HRQoL) and quality‐adjusted time without symptoms of disease or toxicity (Q‐TWiST) results from this trial. Patients and Methods. Patients were randomized to receive six cycles of chemotherapy given every 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 24 publications
0
28
0
3
Order By: Relevance
“…Although some data exist on QoL associated with palliative chemotherapy for advanced gastric cancer6, 7, 8, QoL data associated with surgical palliation are sparse9 10. The aim of this study was to examine the impact of surgical palliation on postoperative QoL in patients with malignant gastric outlet obstruction caused by incurable advanced gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although some data exist on QoL associated with palliative chemotherapy for advanced gastric cancer6, 7, 8, QoL data associated with surgical palliation are sparse9 10. The aim of this study was to examine the impact of surgical palliation on postoperative QoL in patients with malignant gastric outlet obstruction caused by incurable advanced gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The ToGA trial also provided evidence of a prolongation of time to the deterioration of healthrelated quality of life [14]. Furthermore, the subgroup analyses of the ToGA trial restricted to Japanese patients [15] and a subsequent similar phase III study recruiting only Chinese patients [16] have confirmed again such promising results, suggesting the efficacy of trastuzumab irrespective of country of origin.…”
Section: Gastric Cancermentioning
confidence: 85%
“…. Im Vergleich mit der alleinigen Chemotherapie verbesserte die Kombination von Trastuzumab und Chemotherapie auch die Lebensqualität[230].…”
unclassified